A Framework to Characterize Factors Affecting the Adoption of Energy Efficiency Measures Within Electric Motors Systems. (February 2019) - Cagno, Enrico; Accordini, Davide; Trianni, Andrea
Abstract: Electric motor systems account for a remarkable share of total industrial power consumption (even more than 70% in some countries). Despite the wide set of effective opportunities to improve energy efficiency in this cross-cutting technology, the implementation rate is still quite low. Among the barriers affecting the adoption of such measures - identified by previous literature -, little knowledge of the factors that should be taken into account when deciding to undertake an action in this area emerges. Therefore, in the present study we present an innovative framework representing factors affecting the adoption of measures for improved efficiency in electric motor systems. Such factors have been classified according to several categories as follows: compatibility, economic, energy benefits, production-related and operations-related non-energy benefits and losses, synergies, complexity, personnel, and additional technical features, so to fully describe the relevant elements to be considered when considering the adoption of energy efficiency measures (EEMs) in electric motor systems (EMS). The framework may represent a valuable instrument to support industrial decision-makers in the adoption of EEMs for EMS.